PENERAPAN PEMBELAJARAN MODEL SOLUTION AND CRITIC GROUP UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KOMPETENSI DASAR MENGINDENTIFIKASI BENTUK PASAR DALAM KEGIATAN EKONOMI MASYARAKAT PADA MATA PELAJARAN IPS KELAS VIII-B MTs AL-IMAN KLATAKAN SITUBON - Nursalam Nursalam (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2016)
Based on observation result on MTs Al-Iman Klatakan Situbondo, mastery IPS inclined still low far from supposed. Success measuring rod teaches to based in successfully learn 85% to successfully learn classically not yet reached. Based on background, so problem formulation as follows: (1 is applications model study solution and critic group increase student activity in competence base identify market form in subject society economi activity IPS class VIII-B MTs Al-Iman Klatakan Situbondo academic of year 2015/2016?, and (2) is spplications model study solution and critic group increase result learn student in competence base odentify market form in subject society economi activity IPS class VIII-B MTs Al-Iman Klatakan Situbondo academic of year 2015/2016?. Research design was Classroom Action Research that is done 2 cycles. In Classroom Action Research, there 4 stages that is planning, action, observation, and reflection. Primary data by using repetion test, observation with at checklist, and secondary data with interview. Researcher uses target value necessity determine successful as follows: (1) model study applications solution and critic group can increase activity learn to achieve 87%, and (2) model study applications solutiond and critic group can increase result learn to achieve 89%.